KARAKTERISTIK INDIVIDU, KARAKTERISTIK PEKERJAAN DAN PENGALAMAN KERJA, PENGARUHNYA TERHADAP KEMAMPUAN, MOTIVASI DAN KINERJA DOSEN TETAP FISIP UNIVERSITAS BRAWIJAYA MALANG - Alifiulahtin Utaminingsih (Politeknik Negeri Malang, 2018)
This study aims to examine work ability, work motivation and performance based on individual characteristics, job characteristics and work experience of permanent lecturers at FISIP UB Malang. This type of research includes explanatory research that use a quantitative descriptive approach with census methods. Respondents numbered 86 people. The main instrument of the study was a questionnaire using a five-point Likert scale, data analysis using SEM. The results of this study found that: First: There is a significant influence between individual characteristics, job characteristics and work experience on work ability (amounting to 54.8%),. Second: There is a significant influence between individual characteristics, work experience and work ability to work motivation. The contribution of these three variables in explaining variations in work ability is 42.4%, with work ability as the dominant determinant of work motivation. Third: There is a significant effect between individual characteristics, work experience and work motivation on performance, with work motivation as the dominant factor in the high performance of lecturers.